Legal Review of Physician Malpractice Cases: A Narrative Literature Review - Patricia Wulandari; Rachmat Hidayat (HM Publisher, 2022)
This review aimed to discuss legal reviews related to physician malpractice in medical practice. Malpractice is carrying out a profession wrongly or wrongly, which can only form legal responsibility for the maker if it results in a loss determined or regulated by law. Malpractice can occur in carrying out all kinds of professions, including the medical profession. Mistakes in carrying out the medical profession will form criminal or civil legal liability (depending on the nature of the consequences of the losses incurred) containing three main aspects as an inseparable unit, namely treatment that is not according to the norm, done with culpa and causing losses in law. Regarding the doctor not providing services in accordance with professional standards, which then results in disability or death of the patient, this doctor has violated the patient's right to obtain such humane service, so the patient has the right to sue the doctor concerned.